Making researchers moral: Why trustworthiness requires more than ethics guidelines and review. (March 2014) - Johnsson, Linus; Eriksson, Stefan; Helgesson, Gert; Hansson, Mats G
Research ethics, once a platform for declaring intent, discussing moral issues and providing advice and guidance to researchers, has developed over time into an extra-legal regulatory system, complete with steering documents (ethics guidelines), overseeing bodies (research ethics committees) and formal procedures (informed consent). The process of institutionalizing distrust is usually motivated by reference to past atrocities committed in the name of research and the need to secure the trustworthiness of the research system. This article examines some limitations of this approach. First, past atrocities cannot provide the necessary justification unless institutionalized distrust is a necessary or efficient means to prevent future ones – and there are several reasons to doubt this. Second, the efficacy of ethics review in safeguarding morally acceptable research depends on the moral competence and integrity of individual researchers – the very qualities that institutionalized distrust calls into question. Third, ethics guidelines cannot, as is sometimes assumed, educate or guide researchers in moral behaviour unless they already possess considerable capacity for moral judgment. Fourth, institutionalized distrust is a potential threat to the moral competence and integrity of researchers by encouraging a blinkered view of ethical issues, inducing moral heteronomy through incentives, and alienating them to research ethics. We conclude that the moral problem posed by inappropriate short-term behaviour on behalf of researchers is dwarfed by the potential long-term consequences if their moral competence is allowed to deteriorate. Measures must therefore be taken to ensure that researchers are equipped to take their individual responsibility and are not obstructed from so doing.